Engineering students’ English public speaking: Why is it a nerve-wracking experience? - Musrifatun Nangimah (Universitas Islam Sultan Agung, 2022)
Mastering English public speaking is required for Engineering students to contribute to the Ministry of Education’s internationalization policy that is manifested in the university’s regulation. However, English public speaking has become a nerve-wracking experience for L2 learners. This research aims to explore Engineering students’ English public speaking anxiety and its causes. The explanatory sequential design is applied. The online-based survey was conducted on 197 first-semester students and semi-structured interviews with 8 most anxious participants. The triangulation data analysis of quantitative and qualitative phases was carried out. The results illustrate that students experience moderate to low public speaking anxiety levels. The reasons for public speaking anxiety are linguistics problems, inhibition, lack of speaking practice, the difficulty for sentence construction from L1 into the target language, fear of peer negative feedback and being assessed, and dealing with unfamiliar topics as well as speaking delivery driven thoughts. Furthermore, teachers' reflexive identity and the appointment system used to determine public speakers become additional pressures. These findings can be used as valuable consideration to design appropriate speaking pedagogy, especially in the context of English for non-English major programs. Recommendation for future research is discussed.